Pendampingan Digital Marketing dan Copy Writing Bagi UMKM Indutri Kreatif Di Jawa Tengah - Saryatun; helmy, irfan; Riptiono, Sulis; Yordan Hermawan Apidana (LP3M Universitas Putra Bangsa, 2024)
The creative industry in Central Java has experienced significant growth alongside increasing consumer interest in local products. However, many micro, small, and medium-sized enterprises (MSMEs) in the creative industry face challenges in competing in an increasingly competitive market, particularly with the shift towards digital platforms in consumer behavior. Limitations in digital marketing and a lack of proficiency in copywriting are major obstacles for these MSMEs. This community engagement program aims to enhance the capacity of MSMEs in the creative industry to leverage digital platforms for product marketing. Through a series of training sessions and consultations, MSMEs will gain an understanding of digital marketing concepts and effective copywriting techniques. The primary goal of this program is to improve the sustainability of MSMEs in online marketing and increase their revenue. The activities were conducted on January 31, 2024, at the PLUT Cooperative and MSME Building of the Department of Cooperatives and MSMEs of Central Java. The training agenda includes an introduction to digital marketing, SEO, social media marketing, paid advertising, and digital marketing performance measurement. The training materials are designed to provide participants with comprehensive understanding and practical skills in digital marketing for MSMEs in the creative industry